Severe complications after negative pressure wound therapy in burned wounds: two case reports - Ren H; Li Y (Dove Medical Press, 2014)
Haitao Ren,1 Yuan Li21Department of Burns and Wound Center, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People's Republic of China; 2Department of Ultrasound, Women's Hospital, School of Medicine, Zhejiang University, Hangzhou, People's Republic of ChinaAbstract: We present two typical cases of severe complications (sepsis and hemorrhage) after negative pressure wound therapy (NPWT) in burned patients. Necrotic tissues in some deep burn wounds are difficult to judge correctly and remove thoroughly. An electrically burned blood vessel looks “intact” but can easily break. Necrotic tissue or injured blood vessels when using NPWT are dangerous, both for causing sepsis and hemorrhage. This is the first article that reports the severe complications of NPWT in burned patients. It is imperative to heed indications and avoid contraindications. Proper preparation of wound beds, close observation, and sufficient irrigation are also crucial to avoid these severe complications, and there is an urgent need to substitute the central vacuum system with the low-pressure system.Keywords: negative pressure wound therapy, complication, burn sepsis, bleeding, drainage